Kebutuhan Air untuk Tanaman Terung ( Solanum melongena. L) pada Lempung Liat Berpasir di Tanah Ultisols - Ratna Shanti (Universitas Widya Gama Mahakam, 2019)
The purpose of this study was to determine optimum water requirement of eggplant (Solanummelongena L) onsandy clay loam soil of Ultisols during it growth period. The experiment was conducted on 5th May to 27thAgust2017 in glass house Faculty of Agiculture, Mulawarman University, Samarinda. The pot experiment was designed Completely Randomized Design that consisted of four treatments level with seven replications. Treatment based on water avaibility (WA), those are : A = 494 ml (50 % WA), B = 670 ml (75 % of WA) C = 846 ml ( 100 % of WA) and D = 1022 ml ( 125 % of WA).Each experiment pot contained 10 kg dried soil. The treated pots(after watering) have weight respectively, A= 10494 g, B = 10670 g, C= 10846 g, and D= 11022 g. These pots will be weighted every daycontinouslyduring plant growth and maintained those pot weight respectively.Vegetative and generative data were collected and statistical analyzed using variance analysis. If the treatments showed significant different effect, the statistical analysis of those treatment continued by Least Significant Different (LSD) test at 5% level to find out the optimum water requirement level. The results of the experiment showed that treatments of watering was significant effect on the average of vegetative parameters, (vegetative growth i.e.plant height at the age 20, 40, and 60 days, blooming after planting.) and significant effect for generative parameters (fruit number, length and fruit weight).The optimum water requirement for eggplant at 506 ml pot-1 therefore during growth period eggplant needs 40,731 ml of waterfor maximum yield.